PSXI-1 Evaluating the yield and nutritive value of perennial forage species for stockpile grazing of beef cows under western Canadian conditions. (7th December 2018) - Hewitt, B; McGeough, E; Cattani, D; Ominski, K; Crow, G; Wittenberg, K
Abstract: This project assessed the yield and nutritive value of 8 perennial pure grass or pure legume crops and 15 grass-legume binary mixtures for their potential for stockpile grazing of beef cows in Manitoba, Canada. The perennial forage cultivars that were used in the evaluation were: Killarney orchardgrass (K; Dactylis glomerata ); Courtenay tall fescue (C; Schedonorus arundinaceum ); Success hybrid brome (S; Bromus riparius × B. inermis ), cv.'s Fleet (F) and Armada (AR) meadow bromes ( Bromus riparius ); cv.'s Algonquin (AL) and Yellowhead (Y) alfalfa ( Medicago sativa ); and Oxley II cicer milkvetch (O; Astragalus cicer ). The effect of early (ES; June) or late (LS; July) stockpiling of forages was also assessed. Plots (4 replicates/treatment) were seeded at Carman, Manitoba in 2014 in a RCBD and forage measurements conducted in 2015. Mixed treatments were seeded at a 50:50 grass:legume rate. Forages were harvested on October 15 for DM yield (DMY) and subsampled for nutritive value. Courtenay, C+AL, C+Y, and C+O had the highest DMY (P<0.05) for ES ranging from 8, 376 to 10, 274 kg ha -1 with C+O highest overall. For LS, C+O had a higher DMY (6, 508 kg ha -1 ; P<0.05) than any other forage. All ES treatments had higher DMY than the corresponding LS treatments. For ES, few differences in CP between forage treatments were observed excellt all grass only treatments, K+Y, S+Y and F+Y had significantly lower CP values than pure legumes and other mixed treatments. For LS, the legume only, S and S+O, S+AL and S+Y had significantly higher CP than all other treatments (P<0.05), ranging from 147 to 179 g/kg. For NDF, F had the highest mean value across both stockpile treatments, ranging from 597 to 674 g/kg. In conclusion ES Courtenay-legume treatments held the best potential for stockpile grazing beef cows in terms of yield and nutritive value.